Ultrathin exfoliated WS2 nanosheets in low-boiling-point solvents for high-efficiency hydrogen evolution reaction. Issue 1 (February 2020) - Qin, Y Q; Peng, Y Q; Yang, W F; Wang, Y; Cui, J W; Zhang, Y
Abstract: Two-dimensional mono-or few-layer WS2, as a typical transition metal dichalcogenide, usually exhibits excellent electrocatalytic hydrogen evolution reaction (HER) activity. In this work, low-boiling-point solvents are adopted for the controllable preparation of ultra-thin WS2 nanosheets by an improved liquid phase exfoliation process directly from the raw WS2 powder. The thickness of as-obtained WS2 nanosheets is about ∼1.5 nm with lateral size of ∼1.2 μm. Their HER performance was investigated by loading them onto a glass carbon electrode in 0.5M H2 SO4 solution. The resulting polarization and Tafel curves indicate that the as-obtained WS2 nanosheets are effective electrocatalysts for HER with a low onset potential of 65mV and a Tafel slope of 55mV/dec. The proposed liquid phase exfoliation technique is lucrative for exfoliating transition metal disulfide materials in various applications.